Analysing firm-specific and type-specific determinants of eco-innovation - Del Río, Pablo; Romero-Jordán, Desiderio; Peñasco, Cristina (Technological and Economic Development of Economy, 2017)
This paper analyses the main determinants influencing different types of eco-innovations and eco-innovators in Spain. We differentiate between two types of eco-innovations (process vs. product and new-to-the-market (NTM) vs. new-to-the-firm (NTF)) and two different types of ecoinnovators (large vs. small and old vs. new firms). Our findings show that new firms are not more eco-innovative and that smaller firms are certainly less eco-innovative. Although the environmental regulation variable is generally a main driver of eco-innovation, there are specific drivers for some eco-innovator and eco-innovation types. This is the case with internal innovation capabilities, which clearly influence small and new firms to eco-innovate, in contrast to large and old firms. Those capabilities are also a driver of NTM eco-innovation versus NTF eco-innovation. Involvement in external knowledge flows and cooperation is also a crucial variable for small firms to eco-innovate and a main driver of NTM versus NTF eco-innovation. Contrary to expectations, there are a few differential drivers for products vs. process eco-innovations. Energy/material cost reductions and environmental regulation influence both eco-innovation types, whereas the demand-pull from the market is absent for both, probably due to a relatively low degree of environmental consciousness and/or willingness to pay for eco-products by its consumers. First published online: 01 Nov 2015